2014
DOI: 10.1080/09540121.2014.964659
|View full text |Cite
|
Sign up to set email alerts
|

“I have it just like you do”: voices of HIV-negative partners in serodifferent relationships receiving primary care at a public clinic in San Francisco

Abstract: HIV transmission among serodifferent couples has a significant impact on incidence of HIV worldwide. Antiretroviral interventions (i.e., preexposure prophylaxis, post-exposure prophylaxis, and treatment as prevention) are important aspects of comprehensive prevention and care for serodifferent couples. In this study, HIV-negative members of serodifferent couples were interviewed using open-ended questions to explore their health-care needs, perceptions of clinic-based prevention services, and experience of hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Only 4 of the 27 couples (all female-positive) in our study relied exclusively on viral control to prevent dyadic HIV transmission and also reported long-term viral suppression. The HIVnegative members of these couples were acutely aware of their partners' undetectable viral load and had gained confidence through many years of having condomless sex without transmission bolstered by repeated negative HIV tests, a finding also reported by Mahoney et al [73]. These results underscore the need for close long-term monitoring of viral load by providers and their HIV-positive patients in the context of serodifferent couples, as well as the need to consider the psychosocial aspects of prevention strategies among HIV-affected couples.…”
Section: Viral Suppression (Fig 2)supporting
confidence: 58%
See 1 more Smart Citation
“…Only 4 of the 27 couples (all female-positive) in our study relied exclusively on viral control to prevent dyadic HIV transmission and also reported long-term viral suppression. The HIVnegative members of these couples were acutely aware of their partners' undetectable viral load and had gained confidence through many years of having condomless sex without transmission bolstered by repeated negative HIV tests, a finding also reported by Mahoney et al [73]. These results underscore the need for close long-term monitoring of viral load by providers and their HIV-positive patients in the context of serodifferent couples, as well as the need to consider the psychosocial aspects of prevention strategies among HIV-affected couples.…”
Section: Viral Suppression (Fig 2)supporting
confidence: 58%
“…Prior studies have identified several factors associated with inconsistent condom use among HIV-serodifferent couples, including low education and income [26,75], longer duration of the relationship [26], poor mental health and substance use disorders [75][76][77], perceived low HIV risk [78,79], and the desire for sexual pleasure and intimacy [73]. Lack of willingness to use condoms by men [80,81] combined with women's limited agency to negotiate condom use in relationships often marked by gender-based power imbalances or violence has also emerged in the literature as a primary reason for low condom use in mixed status relationships [81][82][83][84][85].…”
Section: Condom Use (Fig 3)mentioning
confidence: 99%
“…The most common indicator for PrEP use among cis women in the U.S. was being in a serodiscordant partnership (Bien, Patel, Blackstock, & Felsen, 2017;Blackstock et al, 2017). Cis women in serodiscordant couples had generally positive feelings about PrEP, as it allowed them to remain HIV negative while maintaining their intimate relationships (Bazzi, Leech, Biancarelli, Sullivan, & Drainoni, 2017;Mahoney, Weber, Bien, & Saba, 2015;Park et al, 2017).…”
Section: Sexual and Relationship Partnersmentioning
confidence: 99%
“…HIV, like other chronic and life-threatening illnesses, can be conceptualized as a “shared illness” given the myriad ways in which it affects others within an individual’s close social network (McDaniel, Hepworth, & Doherty, 2003). Indeed, one’s ability to cope with chronic illness is often predicated on family members’ mobilization in relation to it (Mahoney, Weber, Bien, & Saba, 2014). Likewise, in the case of stigmatizing chronic conditions like HIV, family members might experience the additional burden of “courtesy stigma” (i.e., stigma experienced by associates of those who are infected with the virus; Goffman, 1963) and, perhaps as a result, report avoidant and intrusive thoughts attributable to the disease (Wight, Beals, Miller-Martinez, Murphy, & Aneschensel, 2007).…”
mentioning
confidence: 99%